2022
DOI: 10.3390/insects13050427
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Trichomes and Terpene Compounds in Indigenous and Commercial Thai Rice Varieties against Brown Planthopper

Abstract: Plant trichomes generally act as a physical defense against herbivore attacks and are present in a variety of plants, including rice plants. This research examined the physical and chemical defenses of rice plants against the brown planthopper (BPH), Nilaparvata lugens (Stål) (Hemiptera: Delphacidae). A total of 10 rice varieties were used in this study. An electron microscope was used to observe trichomes. Constitutive and induced volatile compound profiles were assessed using GC-MS analyses. The preference o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…This did not occur in three hybrids (IR80814H, IR81954H, and IR81955H) that showed heterobeltiosis for resistance, thereby further suggesting that quantitative resistance to planthoppers is achievable through the careful selection of parental lines. In our oviposition experiments, plant size affected one of two cases of heterosis for antixenosis resistance; suggesting that there was little effect of breeding on other factors, such as plant volatiles or silicon-based defenses [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ] that are involved in antixenosis resistance. The experiments indicate the importance of separating physiologically-dependent susceptibility (e.g., related to size, growth rates, etc.)…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This did not occur in three hybrids (IR80814H, IR81954H, and IR81955H) that showed heterobeltiosis for resistance, thereby further suggesting that quantitative resistance to planthoppers is achievable through the careful selection of parental lines. In our oviposition experiments, plant size affected one of two cases of heterosis for antixenosis resistance; suggesting that there was little effect of breeding on other factors, such as plant volatiles or silicon-based defenses [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ] that are involved in antixenosis resistance. The experiments indicate the importance of separating physiologically-dependent susceptibility (e.g., related to size, growth rates, etc.)…”
Section: Discussionmentioning
confidence: 86%
“…The experiments indicate the importance of separating physiologically-dependent susceptibility (e.g., related to size, growth rates, etc.) of rice lines from biochemical or other anatomical features, such as surface waxes or leaf hairs [ 48 , 55 , 56 ] that may be more closely associated with specific and heritable herbivore defenses.…”
Section: Discussionmentioning
confidence: 99%
“…In rice, BPH infestation increases VOC emission and changes the profile of VOCs [ 37 ]. Manipulation of volatile emissions in crops has great potential for the control of pest populations.…”
Section: Discussionmentioning
confidence: 99%
“…Macro hairs are observed in silica cells; whereas, micro and glandular hairs are found on stomatal cells or beside the motor cells (Li et al 2010 ). Khetnon et al ( 2022 ) showed that rice can have four types of non-glandular trichomes: prickle, macro, micro and papillae trichomes (Fig. 1 ).…”
Section: Physical Defenses In Ricementioning
confidence: 99%
“…Sandhu and Sarao ( 2021 ) reported that the population of nymphs and adults of BPH were much lower in genotypes with longer and denser trichomes than in susceptible genotypes such as TN1. However, Khetnon et al ( 2022 ) claimed that the physical defense by trichomes was not effective against BPH because trichomes were not tough enough to prevent colonization by the second and third instars. According to Karban et al ( 2002 ), the removal of silicified non-glandular trichomes in rice increased the frequency of damage to leaf sections including the basal region, which was not preferred by the herbivores in the presence of unidirectional structures.…”
Section: Physical Defenses In Ricementioning
confidence: 99%